Intonation in Kannada: some aspects - Manjula (Journal of All India Institute of Speech and Hearing)
The purpose of this study was to analyse the percentage of intelligible responses of a group of listeners to a set of sentences ’spoken’ with specific emotions, and also to analyze the intonation patterns of these sentences. Afrer a series of 3 main pilots, a test list was constructed, which consisted of 36 sentences. 9 emotions (4 pimary, 4 secondary and 1 ’neutral ’) were also selected. Each sentence in the test list was associated with a specific emotion. Each emotion was represented 4 times in the list. The sentences were so selected that some of these sentences could be expressed with 2 different emotions.